Postmastectomy Radiotherapy for Locally Advanced Breast Cancer Receiving Neoadjuvant Chemotherapy. (22nd June 2014) - Meattini, Icro; Cecchini, Sara; Di Cataldo, Vanessa; Saieva, Calogero; Francolini, Giulio; Scotti, Vieri; Bonomo, Pierluigi; Mangoni, Monica; Greto, Daniela; Nori, Jacopo; Orzalesi, Lorenzo; Casella, Donato; et al.
Abstract : Neoadjuvant chemotherapy (NAC) is widely used in locally advanced breast cancer (BC) treatment. The role of postmastectomy radiotherapy (PMRT) after NAC is strongly debated. The aim of our analysis was to identify major prognostic factors in a single-center series, with emphasis on PMRT. From 1997 to 2011, 170 patients were treated with NAC and mastectomy at our center; 98 cases (57.6%) underwent PMRT and 72 cases (42.4%) did not receive radiation. At a median follow-up period of 7.7 years (range 2–16) for the whole cohort, median time to locoregional recurrence (LRR) was 3.3 years (range 0.7–12.4). The 5-year and 10-year actuarial LRR rate were 14.5% and 15.9%, respectively. At the multivariate analysis the factors that significantly correlated with survival outcome were ≥4 positive nodes (HR 5.0, 1.51–16.52; P = 0.035 ), extracapsular extension (HR 2.18, 1.37–3.46; P = 0.009 ), and estrogen receptor positive disease (HR 0.57, 0.36–0.90; P = 0.003 ). Concerning LRR according to use of radiation, PMRT reduced LRR for patient with clinical T3 staged disease (P = 0.015 ). Our experience confirmed the impact of pathological nodal involvement on survival outcome. PMRT was found to improve local control in patients presenting with clinical T3 tumors, regardless of the response to chemotherapy.